A rare variant of generalized granuloma annulare presenting with chronic Epstein-Barr virus infection: coincidence or association? - Song, James E. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2011)
We report a rare variant of generalized granuloma annulare (GGA) in a 62-year-old male patient. The patient presented with large, annular, violaceous patches on the upper arms and thighs. Histological findings were consistent with interstitial granuloma annulare. In addition, high titers of Epstein-Barr Viral Capsid Antigen (EBV VCA) and EBV Nuclear Antigen (EBVNA) antibodies were found. In-situ hybridization did not reveal EBV RNA in the skin lesions. Immune dysregulation in the setting of chronic EBV infection hasbeen suggested as a contributing factor to the development of this rare variant of GGA.
Keywords: Epstein-Barr Virus Nuclear Antigens; Epstein-Barrov virus, jedrni antigeni; Granulom okrogli; Granuloma Annulare; Herpesvirus 4 človeški; Herpesvirus 4, Human; IgG; IgM; In situ hibridizacija; In Situ Hybridization; Middle Age; Srednja leta; virusne infekcije